Protective potential of casein phosphopeptide amorphous calcium phosphate containing paste on enamel surfaces - Somasundaram, Padmini (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Dental caries remains the most common dental disease facing mankind. Prevention of initiation and interruption in progression of early lesions are the desirable modes of caries management. There is a scope for agents, which may be used to enhance anti - caries activity. This need has redirected research to develop novel preventive agents that can act as an adjunct to fluoride or independent of it. Casein Phosphopeptide – Amorphous Calcium Phosphate (CPP-ACP) is one such agent that has been proposed to have anti cariogenic properties. AIM: The purpose of this in vitro study was to evaluate the effect of paste containing CPP-ACP, MI Paste, on enamel remineralization. MATERIALS AND METHODS: This study consisted of 30 samples embedded in orthodontic resin with either the buccal or lingual surface exposed. The samples were assigned to either a CPP-ACP containing paste; Fluoridated toothpaste; or a control group. The groups were then subjected to cycling in a demineralizing solution and a remineralizing solution. Groups II and III received prior application of MI paste and Fluoridated toothpaste respectively followed by cycling in a demineralizing solution and a remineralizing solution. Following 14 days of cycling, the samples were sectioned and examined using confocal microscopy. The lesion depth, were evaluated. STATISTICAL ANALYSIS: Image Proplus software was used to analyze the images. The values were statistically evaluated using one – way ANOVA and Scheffe's Test. RESULTS AND CONCLUSION: Within the limitations of the study it was concluded that enamel surfaces treated with the CPP-ACP paste exhibited the least lesion depths followed by the enamel surfaces treated with the fluoridated tooth paste and control group respectively.